Supplier-Supplier Relationships in the Buyer-Supplier Triad: Building Theories from Eight Case Studies - Wu,Zhaohui; Choi,T.Y. (Journal of Operations Management, 2005)
Many researchers have studied how the buying company manages its relationship with suppliers (i.e. buyer”supplier relationship). Extending this genre of study, researchers have recently shown interest in investigating how the buying company manages relationships between the suppliers (i.e. supplier”supplier relationship). In other words, just as the relationship with the suppliers does, the relationships between suppliers have strategic implications for the buyer. We present in this study eight cases that describe supplier”supplier relationship dynamics. Using theory building through case studies, we identify five archetypes of supplier”supplier relationships. Each type of relationship is a unique configuration of the relational characteristics. We also present working propositions that associate the antecedent conditions that lead to these archetypes and eventual performance implications.
Keywords: Supply Chain